Current status of awareness and use the phenomenon of students’ language code-mixing and the issue of preserving the purity of the Vietnamese language - Vinh, Le Thi Thuy (Journal of Asian Scientific Research, 2024)
In this article, we set out to survey the current state of awareness and use of the phenomenon of language code-mixing among young people, thereby assessing the causes and effects and providing directions in language use by contemporary Vietnamese youth. Currently, code-mixing is a very common phenomenon in young people’s communication, especially pupils and students in high schools and universities. Code-mixing is not only a purely linguistic phenomenon but also a phenomenon recognized in language-cultural contact. This phenomenon has created a lot of mixed public opinion. This phenomenon significantly contributes to maintaining the purity of the Vietnamese language in contemporary times. By using statistical methods based on questionnaires administered to over 1,000 students at Vietnamese universities, we have obtained results regarding the current status of awareness and use of code-mixing phenomenon in the language. The results obtained show that young people in Vietnam have relatively correct awareness about the use of language code mixing phenomenon, but there is still a need for measures to orient a part of young people to improve their language skills. I highly recommend the use of code-mixing phenomenon in particular and modern languages in general. The three measures proposed in the article, namely raising awareness among young people, promoting language education, and coordinating between relevant parties, will certainly contribute to the work of preserving the purity of the Vietnamese language.